A retrospective multicenter study on clinical and serological parameters in patients with MuSK myasthenia gravis with and without general immunosuppression - Koneczny, Inga; Mané-Damas, Marina; Zong, Shenghua; De Haas, Sander; Huda, Saif; van Kruining, Daan; Damoiseaux, Jan; De Rosa, Anna; Maestri, Michelangelo; Guida, Melania; Molenaar, Peter; Van Damme, Philip; et al. (Frontiers in Immunology, 2024)
Muscle-specific kinase (MuSK)- myasthenia gravis (MG) is caused by pathogenic autoantibodies against MuSK that correlate with disease severity and are predominantly of the IgG4 subclass. The first-line treatment for MuSK-MG is general immunosuppression with corticosteroids, but the effect of treatment on IgG4 and MuSK IgG4 levels has not been studied. We analyzed the clinical data and sera from 52 MuSK-MG patients (45 female, 7 male, median age 49 (range 17-79) years ) from Italy, the Netherlands, Greece and Belgium, and 43 AChR-MG patients (22 female, 21 male, median age 63 (range 2-82) years) from Italy, receiving different types of immunosuppression, and sera from 45 age- and sex-matched non-disease controls (with no diagnosed diseases, 38 female, 8 male, median age 51.5 (range 20-68) years) from the Netherlands. We analyzed the disease severity (assessed by MGFA or QMG score), and measured concentrations of MuSK IgG4, MuSK IgG, total IgG4 and total IgG in the sera by ELISA, RIA and nephelometry. We observed that MuSK-MG patients showed a robust clinical improvement and reduction of MuSK IgG after therapy, and that MuSK IgG4 concentrations, but not total IgG4 concentrations, correlated with clinical severity. MuSK IgG and MuSK IgG4 concentrations were reduced after immunosuppression in 4/5 individuals with before-after data, but data from non-linked patient samples showed no difference. Total serum IgG4 levels were within the normal range, with IgG4 levels above threshold (1.35g/L) in 1/52 MuSK-MG, 2/43 AChR-MG patients and 1/45 non-disease controls. MuSK-MG patients improved within the first four years after disease onset, but no further clinical improvement or reduction of MuSK IgG4 were observed four years later, and only 14/52 (26.92%) patients in total, of which 13 (93.3%) received general immunosuppression, reached clinical remission. We conclude that MuSK-MG patients improve clinically with general immunosuppression but may require further treatment to reach remission. Longitudinal testing of individual patients may be clinically more useful than single measurements of MuSK IgG4. No significant differences in the serum IgG4 concentrations and IgG4/IgG ratio between AChR- and MuSK-MG patients were found during follow-up. Further studies with larger patient and control cohorts are necessary to validate the findings.